+0  
 
0
154
3
avatar

solve for x in terms of y and z, assuming y does NOT equal 3:

 

\( xy = 3x + 2y + z\)

 

thanks! i'm rly having trouble :((

 Dec 21, 2019
 #1
avatar+60 
0

First we get all x on one side: xy-3x = 2y+z

Then we factor x on the left hand side: x(y-3)

then divide by y-3

 Dec 21, 2019
 #2
avatar
0

right, but what about the right side? is it just 2y+z / y-3?

 Dec 21, 2019
 #3
avatar+111360 
+1

xy  = 3x  + 2y  + z        rearrange as

 

xy - 3x  =   2y + z          factor out x on the left

 

x ( y - 3)  = 2y + z          divide both sides by  (y - 3)

 

          2y + z

x =    ______

          y  - 3  

 

 

cool cool cool

 Dec 21, 2019
edited by CPhill  Dec 21, 2019

19 Online Users

avatar
avatar
avatar
avatar
avatar